1990
DOI: 10.1002/aja.1001880106
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescence localization of vinculin in ectoplasmic (“junctional”) specializations of rat sertoli cells

Abstract: We have investigated, using indirect immunofluorescence techniques, the possibility that vinculin is a component of Sertoli cell ectoplasmic specializations. Affinity-purified polyclonal antibodies produced against human platelet vinculin were used to probe fixed frozen sections of rat testis. Specific fluorescence occurs in Sertoli cell regions adjacent to spermatids and to basally situated junctional complexes, sites at which ectoplasmic specializations are known to occur. Staining also occurs in Sertoli cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 52 publications
5
47
0
Order By: Relevance
“…Therefore, double immunofluorescence was performed using the constitutional and marker proteins for TBC, actin and vinculin (Grove et al, 1990;Mulholland et al, 2001;Chapin et al, 2001;Guttman et al, 2004a;Lee and Cheng, 2004a;. As expected, actin and vinculin were colocalized with dynamin 2 at the apical regions of Sertoli cells in stage VII (Fig.…”
Section: Amphiphysin 1 and Dynamin 2 Colocalize At Tbc Structuressupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, double immunofluorescence was performed using the constitutional and marker proteins for TBC, actin and vinculin (Grove et al, 1990;Mulholland et al, 2001;Chapin et al, 2001;Guttman et al, 2004a;Lee and Cheng, 2004a;. As expected, actin and vinculin were colocalized with dynamin 2 at the apical regions of Sertoli cells in stage VII (Fig.…”
Section: Amphiphysin 1 and Dynamin 2 Colocalize At Tbc Structuressupporting
confidence: 53%
“…TBCs are present in a variety of mammals including rat, mouse, hamster, rabbit, dog, monkey and human (Russell and Malone, 1980). In rat, TBCs were observed at the luminal region of stage VII seminiferous tubules (Russell, 1979b), where they are enriched in cell cytoskeletal and adherent molecules such as actin, vinculin, cofilin, cortactin, nectin, and cadherin (Grove et al, 1990;Mulholland et al, 2001;Chapin et al, 2001;Guttman et al, 2004a;Lee and Cheng, 2004a;. As to the cell biological function of TBC, two possibilities have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, numerous studies have linked focal contact function to cell spreading and migration. Although the existence of focal contacts in the testis has never been described, several studies from different laboratories have reported the presence of putative focal contact proteins in this organ, including ␣6␤1 integrin (Salanova et al, 1995(Salanova et al, , 1998Mulholland et al, 2001), integrin-linked kinase [ILK (Mulholland et al, 2001)], focal adhesion kinase [FAK (Siu et al, 2003)], c-Src Zhang et al, 2005), vinculin (Grove et al, 1990;Pfeiffer and Vogl, 1991), profilin III (Braun et al, 2002), talin (Santoro et al, 2000), paxillin (Wine and Chapin, 1999), zyxin , fimbrin (Grove and Vogl, 1989), and laminin (Koch et al, 1999;Siu and Cheng, 2004a;Yan and Cheng, 2006). It is noteworthy that many of these focal contact proteins were shown to localize to the ectoplasmic specialization rather than at the Sertoli cell-basement membrane interface, as expected.…”
Section: Cell-matrix Actin-based Focal Contactsmentioning
confidence: 99%
“…So far, a growing list of proteins has been shown to underlie ectoplasmic specialization function including ␣6␤1 integrin (Palombi et al, 1992;Salanova et al, 1995;Mulholland et al, 2001), laminin , actin (Vogl et al, 1993), ␣-actinin (Russell and Goh, 1988), myosin VIIA (Hasson et al, 1997), fimbrin (Grove and Vogl, 1989), espin (Bartles et al, 1996), vinculin (Grove et al, 1990;Pfeiffer and Vogl, 1991), phosphorylated c-Src , paxillin (Mulholland et al, 2001), gelsolin , cadherin , ILK (Mulholland et al, 2001), phosphorylated FAK (Siu et al, 2003), testin (Grima et al, 1998), and Keap1 Velichkova et al, 2002) (Fig. 1).…”
Section: The Ectoplasmic Specialization a Testis-specific Anchorimentioning
confidence: 99%
See 1 more Smart Citation